Tinjauan Penyimpanan Rekam Medis Di Ruang Filling Puskesmas Karang Mulya Kecamatan Bojongmangu Kabupaten Bekasi - Rifqi Fauzan; Noor Yulia; Laela Indawati; Puteri Fannya (Yayasan Literasi Sains Indonesia, 2022)
The medical record storage system is very important to do in health care institutions, because it can make it easier for medical records to be stored in storage racks, speed up finding or retrieval and return, and protect medical records from theft, physical, chemical, and biological damage. The purpose of this study was to find out how the implementation of medical record storage in the filing room at Karang Mulya Health Center, Bojongmangu District, Bekasi Regency. The research method uses descriptive qualitative analysis method with the main informant being the head of the Puskesmas, other informants in charge of the medical record room, and medical record staff. The results of the study show that there is no standard operating procedure for storing medical records specifically for internal health centers, the results of the analysis of the storage space capacity can accommodate 30,000 medical records, and currently there are 16,319 medical records. The storage rack is still sufficient if there is a new medical record. The problem factor is in the filing room, the preparation of medical records is still stacked not in a row, and the medical records used are not immediately returned to the shelves, there has been no retention since 2017. Suggestions for standard operating procedures for storage procedures are made for internal health centers. Evaluate and improve the placement of medical records according to the applicable standards in the filing room.